Strengthening Generation Z’s Eco-literacy through the Processing of Organic Waste into Eco-Enzymes: An Actualization of an Impactful Campus - Damianus Dai Koban; Erian Fatria; Iratna Dewi; Winarti Winarti; Agus Priadi; Febrian Rahmat Suwandi SN; Tika Ramadanti; Yova Fizatul Hasanah; Fajri Kurniawan (Universitas Negeri Gorontalo, 2026)
The environmental harm caused by the disorganized amounts of rubbish, particularly in Indonesian cities like Bukittinggi, is the basis for the significance of implementing the community service program. This buildup is directly linked to Bukittinggi's growing population each year. This community service project aims to educate Generation Z about efforts to turn organic waste into something useful and advantageous for the environment and society. Purposive sampling was employed to choose 15 members of Generation Z from Universitas Prima Nusantara Bukittinggi for this community service program, which uses a blended learning–based counseling approach. After the training, the participants were given a tool to measure their understanding of environmental issues related to turning waste into eco-enzymes, based on the WTP (Waste to Product) concept. This community service project used a set of 18 calibrated eco-literacy instruments to obtain descriptive data on the level of environmental literacy of the activity participants. The data analysis was descriptive, illustrating the dynamics of eco-literacy among participants after receiving material and demonstrations on processing waste into eco-enzymes. The results of this community service program provided students with new experiences through activities organized by the team, which demonstrated greater interest and curiosity. Environmental literacy tests showed that, overall, Generation Z participants had a high level of eco-literacy (around 66.67%), meaning that, in general, these activities have led participants to develop a deep awareness of the importance of managing waste before disposing of it in the surrounding environment. In conclusion, this training method contributes to improving environmental literacy and waste management skills for Generation Z, so that they can be empowered and continue to achieve sustainable cities.